Dietary patterns and their associations with obesity among 4–9-year-old children in the United Arab Emirates: A cross-sectional study - Farah Naja; Nada Abbas; Leila Itani; Fatima Al Zahraa Chokor; Leila Cheikh Ismail; Ayesha S. Al Dhaheri; Lynda O’Neill; Samer Kharroubi; Habiba I. Ali; Maysm N. Mohamad; Nahla Hwalla; Lara Nasreddine (PLoS ONE, 2026)
Dietary patterns constitute a modifiable lifestyle exposure, affecting obesity among children. This study aimed to identify and characterize dietary patterns amongst young school-aged children in the UAE and investigate their association with obesity. A cross-sectional survey of 4–9-year-old children (n = 426) was conducted in the 3 major Emirates of the UAE. Socio-demographic characteristics and anthropometric measurements were obtained. Dietary assessment was performed using the 24-hour recall method. Derivation of dietary patterns was carried out using factor analysis. Of the study sample, 19.5% were overweight/at risk of overweight, and 5% were obese. Two main dietary patterns were derived: “Healthy Pattern”, marked by higher consumption of fruits and vegetables, olive oil, and whole grains, and “Western Pattern,” characterized by higher intakes of fast food, salty snacks, sweets, and sugar-sweetened beverages. The Healthy Pattern demonstrated negative correlations with total energy, saturated and trans-fat intake, and a positive correlation with dietary fiber intake. The Western Pattern was positively correlated with proteins, cholesterol, saturated and trans-fat intake, and negatively correlated with dietary fiber intake. Higher scores of the Healthy Pattern were associated with lower BMI-for-age Z scores. These findings provide evidence for the development of culture-specific nutrition programs for curbing the obesity epidemic amongst children in the UAE.